A Critique of Debt Financing for Local Governments - Daniel Hummel (Indonesian Management and Accounting Research, 2011)
The dichotomy between pay-as-you-go (taxation financing) and pay-as-you-use (debt financing) methods of financing municipal projects, etc, is the area of concern in this paper. While there arc advantaees and disadvantages to both forms, debt financing carries a considerable amount of baggage known as interest. Interest or usury has been a concern of economic and religious thinkers through the ages. Given the potentially negative effect this has on the debtor, Indonesia is forewarned as it decentralizes fiscal administration to local governments. Besides reliance on taxation financing, an alternative public debt option is highlighted.